Multi-omics characterization of silent and productive HPV integration in cervical cancer - Junpeng Fan; Yu Fu; Wenju Peng; Xiong Li; Yuanming Shen; Ensong Guo; Funian Lu; Shengtao Zhou; Si Liu; Bin Yang; Xu Qin; Dianxing Hu; et al. (Elsevier, 2023)
Summary: Cervical cancer (CC) that is caused by high-risk human papillomavirus (HPV) remains a significant public health problem worldwide. HPV integration sites can be silent or actively transcribed, leading to the production of viral-host fusion transcripts. Herein, we demonstrate that only productive HPV integration sites were nonrandomly distributed across both viral and host genomes, suggesting that productive integration sites are under selection and likely to contribute to CC pathophysiology. Furthermore, using large-scale, multi-omics (clinical, genomic, transcriptional, proteomic, phosphoproteomic, and single-cell) data, we demonstrate that tumors with productive HPV integration are associated with higher E6/E7 proteins and enhanced tumor aggressiveness and immunoevasion. Importantly, productive HPV integration increases from carcinoma in situ to advanced disease. This study improves our understanding of the functional consequences of HPV fusion transcripts on the biology and pathophysiology of HPV-driven CCs, suggesting that productive HPV integration should be evaluated as an indicator of high risk for progression to aggressive cancers.